2006
DOI: 10.2136/sssaj2006.0003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Manure Phytic Acid on Phosphorus Solubility in Calcareous Soils

Abstract: Manure characteristics can influence the potential for P transfer in runoff following land application of manures. This research assessed the influence of manure characteristics on P solubility in calcareous soils using manures from poultry (Gallus Domisticus) fed a variety of grain-based diets with the manures containing a range of total P (5.6-16.4 g P kg-1), water-extractable P (WEP, 0.9-4.7 g P kg -1), phytic acid P (0.1-7.6), total N/P ratios (2.6-5.1), and total C/P ratios (19.5-75.7). In addition, mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 45 publications
4
32
1
Order By: Relevance
“…This finding supports previous work where analysis of excreta from broilers fed diets containing various cultivars of barley revealed that only trace amounts of phytate P were excreted, irrespective of the phytate P concentration of the initial feed (Leytem et al, 2007). However, as the diets in the studies by Maguire et al (2004) and Leytem et al (2006) also contained appreciable amounts of inorganic Ca and P, it could be expected that differences in the proportion of phytate P in the excreta were due to the detrimental effects of these minerals on intestinal phytate P hydrolysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding supports previous work where analysis of excreta from broilers fed diets containing various cultivars of barley revealed that only trace amounts of phytate P were excreted, irrespective of the phytate P concentration of the initial feed (Leytem et al, 2007). However, as the diets in the studies by Maguire et al (2004) and Leytem et al (2006) also contained appreciable amounts of inorganic Ca and P, it could be expected that differences in the proportion of phytate P in the excreta were due to the detrimental effects of these minerals on intestinal phytate P hydrolysis.…”
Section: Discussionsupporting
confidence: 91%
“…Maguire et al (2004) reported that litter from birds fed maize-based diets contained 0.26-0.56 of P as phytate P, while concentrations in manure from layers fed maize-based diets ranged from 0.35 to 0.80 of total P (Leytem et al, 2006). Based on these findings, it was expected that there would be reasonable concentrations of phytate P in the excreta in the present study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, manures that have a greater proportion of phytate P will have decreased WSP concentrations and WSP:TP. Examination of the available literature reveals a similar trend in swine feces (Baxter et al, 2003;Leytem and Thacker, 2008), broiler litter (Maguire et al, 2004;Toor et al, 2005), and manure from laying hens (Leytem et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, one would expect that storage of the manures in the present study would result in a further decrease in phytate content, possibly resulting in an increase in manure WSP. Additionally, Leytem et al (2006) reported that once manures are incorporated into soils, the manure phytate will break down over time, releasing soluble P, thereby ameliorating differences in manure WSP attributable to phytate content. Although the feces from the swine fed the corn diet had greater concentrations of phytate, and therefore less soluble P, the breakdown of phytate in storage and soils will release soluble P over time and will therefore ameliorate any benefits of this reduction in WSP.…”
Section: Discussionmentioning
confidence: 99%